PENGARUH KONSUMSI SUSU KEDELAI TERHADAP KELUHAN MENOPAUSE - Anggrahini, Kunthy; Akademi Kebidanan Estu Utomo Boyolali, Sri Handayani (Jurnal Kebidanan, 2014)
ABSTRACT Women older than 45 years will experience a decrease in estrogen and progesterone hormones that cause menopause. 80% of women experiencing menopausal complaints such as hot flushes, cold sweats at night, often restless, irregular bleeding, bone loss and vaginal drying. So far it has done a variety of things to resolve complaints at the time of menopause, such as the provision of health education. And the reduction of complaints ranging from the simple physical exercises such as sports and exercise, adequate rest patterns, nutrition and diet, as well as hormonal therapy for estrogen in the body hold back. One of nutrition therapy at menopause is consume food that are rich in phytoestrogens. that is processed from soybeans are soy milk, which also contains isoflavones to reduce menopausal complaints.To determine the relationship of soy milk consumption on menopausal complaints.This quasi-experimental study with a type of pre-test and post-test with control group design with case-control approach. This study population is all the mothers in the village of menopause Tegaljaro number of 49 respondents, with purposive sampling technique with a sample of 30 mothers and pairet t test analysis of the data.Before the menopause are given soy milk complaints most have a value of 12 which is 13 respondents (43,3%), Once given soymilk most complaints menopause gets a value of 12 are 8 repondents (26,7%) andÂ  1 respondent (3,3%) by value 3. Calculation pariet t test with Î± = 0.05, the value of X2 count 19 286 and p value = 0.001 (p <0.05), mean Ha Ho accepted and rejected. It was concluded that there is a relationship of soy milk consumption on menopausal complaints. Keywords: Consumption of soy milk, menopausal complaints